1998
DOI: 10.1046/j.1365-2222.1998.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled and nasal nitric oxide is increased in laboratory animal allergy

Abstract: Background Allergens from rats, mice, guinea pigs or rabbits cause up to 30% of exposed persons to develop specific immunoglobulin E (IgE) responses. Laboratory animal allergy (LAA) is among the highest occupational risks for asthma in the UK. Elevated levels of nitric oxide (NO) are found in exhaled breath in asthma. In LAA symptoms may progress from conjunctivitis, rhinitis to asthma. Health surveillance aims to detect early sensitization. Objective To assess whether an association exists between LAA and exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 18 publications
4
27
0
Order By: Relevance
“…The level of exhaled NO (eNO) can vary considerably between individuals, but is consistently found to be increased in asthmatic patients and atopic subjects [2,5,6,9,16,40]. In addition, eNO may be a sensitive marker for respiratory effects related to air pollution, as we previously showed a positive association (P<0.001) between the level of ambient air pollution and eNO level [38].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The level of exhaled NO (eNO) can vary considerably between individuals, but is consistently found to be increased in asthmatic patients and atopic subjects [2,5,6,9,16,40]. In addition, eNO may be a sensitive marker for respiratory effects related to air pollution, as we previously showed a positive association (P<0.001) between the level of ambient air pollution and eNO level [38].…”
Section: Introductionmentioning
confidence: 77%
“…Nevertheless, high eNO values are consistently observed in allergic-asthma patients and atopic individuals [2,5,6,9,16,40], though the physiological meaning of this increase in eNO is still not understood. Increased production and release of NO in the airways might represent a broncho-dilating feedback effect to counteract broncho-constriction in asthma, or might reflect the characteristic pulmonary inflammatory reaction of asthmatic lungs.…”
Section: Discussionmentioning
confidence: 95%
“…eNO levels may be elevated in patients before asthmatic symptoms develop [8,9]. HENRIKSEN et al [8] and GRATZIOU et al[9] observed a seasonal rise in eNO levels in pollensensitised subjects with and without rhinitic and/or asthmatic symptoms, with a tendency towards increased concentrations in symptomatic subjects.Despite the considerable number of publications and results indicating relations between baseline eNO level and/or eNO changes on the one hand and symptoms [9][10][11], bronchial hyperresponsiveness [12,13] and inflammatory parameters of the airways [14] on the other, the clinical role of eNO measurements has not been exactly defined. Moreover, the relation between eNO levels and eNO changes following laboratory allergen challenge has so far rarely been compared between subjects with rhinitic and those with asthmatic responses.…”
mentioning
confidence: 99%
“…Despite the considerable number of publications and results indicating relations between baseline eNO level and/or eNO changes on the one hand and symptoms [9][10][11], bronchial hyperresponsiveness [12,13] and inflammatory parameters of the airways [14] on the other, the clinical role of eNO measurements has not been exactly defined. Moreover, the relation between eNO levels and eNO changes following laboratory allergen challenge has so far rarely been compared between subjects with rhinitic and those with asthmatic responses.…”
mentioning
confidence: 99%
“…In the present study we investigated the possibility that a potent exudative and vasodilator stimulus like histamine topically given to the nasal mucosa in healthy individuals may increase nasally exhaled NO as seen in allergic rhinitis [5,10,24].…”
Section: Discussionmentioning
confidence: 99%